Drivers Drowsiness Detection with Speed Limiter Integrated Fatigue Anlyzer (SLIFA) on Fuel Tank Truck - Pranoto, Hadi; Leman, A M; Sukmajati, Danto; Hanum, Bethriza; Baba, Ishak (International Journal of Integrated Engineering, 2018)
Traffic accident is becoming the most serious problem in Indonesia as it happens every day and every time. It was proved by increasing fatalities from 321,301 to 85,596 accident cases. It means that there are 10 road fatalities per day.Â There are several factors that cause traffic accident, such as external 34%, attitude 24%, fatigue 20%, over speed 17%Â and technical vehicle 5%. Other factors might be caused by rapid growth of vehicles and industries which increase significantly. The average annual vehicle growth from 1996 to 2006 is 20% , which might take a higher possibility in increasing road fatalities. The method is to pair SLIFA on the fuel tank truck engine to control the driver’s physical condition through the heartbeat of the driver with a sensor that has been placed directly in front of the driver and when the driver drowsiness speed will decrease up to 30 km /h. The result of this research is the decrease of accident ignored by sleepy driver from shift of incident data during January-Juny 2016 period there are 51 cases of Shift of incident that is in morning 20%, afternoon 33%, night 25%, daylight 22%, then after the SLIFA pair decreased the case shift of incident to 39 cases, consisting of 13% morning, 59% afternoon, night 23% and daylight 5%, a total decrease in incident shift by 76% in July 2016-January 2017 so SLIFA to be very effective at attach to the fuel tank truck in reducing the drivers drowsiness. What needs to be done in future research is how to get SLIFA integrated with image processing.